Who Pays for Climate Loss and Damage? State Obligations Under International Law Explained - Damanik, Yeriko Anugrah Pratama; Sudibya, Dafa Pranaja Sarwahita; Wicaksono, Sonny Saptoajie; Abidah, Shofriya Qonitatin; Masyhar, Ali; Wulandari, Cahya; Wilson, Jack Andrew; Rahman, Aisha Nur (Indonesian Journal of Environmental Law and Sustainable Development, 2024)
Climate change has intensified debates over responsibility for loss and damage suffered by states and communities most vulnerable to its impacts. Rising sea levels, extreme weather events, ecosystem degradation, and economic disruption have generated irreversible harms that cannot be addressed solely through mitigation and adaptation. This article examines the central question of who should bear responsibility for climate-related loss and damage under international law, with a particular focus on the obligations of states. It analyzes the legal foundations of state responsibility, including principles of common but differentiated responsibilities (CBDR), equity, due diligence, and the prevention of transboundary harm. The study situates loss and damage within the framework of key international instruments such as the United Nations Framework Convention on Climate Change, the Paris Agreement, and decisions of the Conference of the Parties, including the establishment of mechanisms addressing loss and damage. It explores how customary international law and emerging climate jurisprudence contribute to clarifying states’ duties, particularly in relation to historical emissions, capacity to respond, and the protection of vulnerable populations. The article also considers the role of compensation, financial assistance, and international cooperation as potential expressions of legal and moral accountability. While international law does not yet provide a comprehensive or enforceable regime for climate loss and damage, the analysis demonstrates that evolving legal norms increasingly recognize differentiated state obligations. The article argues that developed states, due to their greater historical contributions to climate change and superior resources, bear heightened responsibilities to support affected states through finance, technology transfer, and capacity-building. Ultimately, the paper concludes that addressing climate loss and damage requires strengthening legal accountability while fostering equitable cooperation to ensure climate justice and sustainable development for present and future generations.